OIL PRICE FLUCTUATIONS AND THEIR IMPACT ON THE RETURN OF THE IRAQ STOCK EXCHANGE INDEX (ISX60) WITH A TEMPLATE FRAMEWORK (COPULA-COVAR-MODWT) * FOR THE PERIOD (2/1/2020-31/3/2023) - Dheyaa Mohammed Abed; Ali Ahmed Faris (Scholars Digest Publishing, 2023)
The aim of the research is to explain the impact of crude oil price fluctuations on the return of the Iraq Stock Exchange Index (ISX60), as well as to explain the most important factors that lead to the occurrence of these fluctuations, with the aim of examining the long-term and short-term impact of oil markets on the Iraq Stock Exchange Index (ISX60). This point indicates the importance of understanding the complex relationship between oil prices and stock markets and how they change over time. This can help investors and decision makers develop better investment strategies and understand expected volatility in financial markets as these investigations provide evidence of the impact of crude oil prices on the financial sector. Some studies were mentioned that focused mainly on the variables of the study, as daily data was collected for the period extending from 1/2/2020 until 3/31/2023, with a number of views (1185), and this research focuses on studying the impact of oil price fluctuations on the return of the index. The Iraqi Stock Exchange (ISX60), as well as measuring and estimating the relationship between oil prices and the (1SX60) index by employing marginal distribution models represented by the Copula-CoVaR model and wavelet analysis represented by the Maximal Overlap discrete wavelet transform model to describe and analyze the model. Dependence (mutual correlation) between the research variables, that is, between oil prices as an independent variable and the returns of the Iraq Stock Exchange Index (ISX60) as a dependent variable. The research concluded that the volatility of the oil market positively and strongly affects the return of the Iraqi Stock Exchange index and that this relationship is moral and statistically significant, i.e., an increase in oil prices is accompanied by an increase in the return of the Iraqi Stock Exchange index and vice versa. Therefore, the fluctuations of oil prices towards the return of the Iraqi Stock Exchange Index are very positive and strong in the short term, but the strength of this positive relationship soon decreases in the long term, according to the changing MODWT values during the different levels.